Adult Lineage Restricted CNS Progenitors Specify Distinct Glioblastoma Subtypes - Alcantara Llaguno, Sheila R. (Cancer Cell, 2015)
A central question in glioblastoma multiforme (GBM) research is the identity of the tumor-initiating cell, and its contribution to the malignant phenotype and genomic state. We examine the potential of adult lineage restricted progenitors to induce fully penetrant GBM using central nervous system (CNS) progenitor-specific inducible Cre mice to mutate Nf1, Trp53 and Pten. We identify two phenotypically and molecularly distinct GBM subtypes governed by identical driver mutations. We demonstrate that the two subtypes arise from functionally independent pools of adult CNS progenitors. Despite histologic identity as GBM, these tumor types are separable based on the lineage of the tumor-initiating cell. These studies point to the cell of origin as a major determinant of GBM subtype diversity.